2021
DOI: 10.3389/fpsyg.2021.629231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Methods for Service-Learning Projects in Engineering in Higher Education: A Systematic Review

Abstract: Service-learning (SL) helps engineering students to be involved in community activities and to be motivated by their studies. Although several reviews and research studies have been published about SL, it is not widespread in sciences and engineering at the university level. The purpose of this research is to analyze the different community services or projects where SL is implemented by engineering students and faculty and to identify the procedures that were usually implemented to assess SL-based courses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 55 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…These carry out accreditation processes in engineering, which include the importance of environmental sustainability [22]. This means that universities are constantly in educational innovation processes and always keeping in mind the demands of the planet that are disclosed from the UN [37].…”
Section: Discussionmentioning
confidence: 99%
“…These carry out accreditation processes in engineering, which include the importance of environmental sustainability [22]. This means that universities are constantly in educational innovation processes and always keeping in mind the demands of the planet that are disclosed from the UN [37].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the question referring to the overall assessment, the teachers stated that they were very satisfied. Their reflection focused on the idea that most engineers would play an active role in the improvement of their surrounding area, if they could, and agricultural engineers might therefore consider playing active roles to improve the rural environment in which they work, an aspect that could be instilled in the students through S-LP experiences and which is the final objective of this type of teaching experience in engineering [24,29]. The teachers also highlighted the social awareness achieved through the S-LP.…”
Section: Personal Opinionmentioning
confidence: 99%
“…And an agricultural engineer designs crops to provide food and infrastructures that develop the rural environment and improve rural living conditions. This perception is also not helped by the high number of concepts that have to be explained on technical university courses [22], generally of a very varied nature that are hardly conducive to focusing this type of activity on a specific social issue [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the temporal co-word analysis indicated that this is not a recent phenomenon. Indeed, systematic reviews of research were recently published on the use of service learning in engineering education from the perspectives of community engagement [178] and assessment [179]. Nonetheless, given the knowledge and experience that has accumulated on the use of service learning in engineering education, we believe that it would be timely to conduct reviews of research that clarify, summarize, and consolidate what has been learned from the in-depth implementation of service learning in this domain.…”
Section: Implications Of the Findingsmentioning
confidence: 99%